2023
DOI: 10.1186/s12933-022-01732-0
|View full text |Cite
|
Sign up to set email alerts
|

The impact of triglyceride-glucose index on ischemic stroke: a systematic review and meta-analysis

Abstract: Background Strokes significantly impair quality of life and incur high economic and societal burdens. The triglyceride and glucose (TyG) index is a biochemical marker of insulin resistance (IR) and may have important value in the prediction of strokes, especially ischemic stroke (IS). Our study aims to investigate the relationship between TyG index and IS and ascertain whether TyG index is independently associated with IS adverse outcomes. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
29
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(33 citation statements)
references
References 75 publications
4
29
0
Order By: Relevance
“…36 Yang et al included a total of 592 616 individuals in their meta-analysis and discovered the correlation between TyG index and ischaemic stroke in the general population. 37 In numerous large-scale clinical observational studies, it has been shown that the incidence of post-PCI MACE and TyG index are positively correlated. [38][39][40] There is a correlation between TyG index and prevalence of MACE in post-PCI populations; however, results of these studies have been inconsistent.…”
Section: Discussionmentioning
confidence: 99%
“…36 Yang et al included a total of 592 616 individuals in their meta-analysis and discovered the correlation between TyG index and ischaemic stroke in the general population. 37 In numerous large-scale clinical observational studies, it has been shown that the incidence of post-PCI MACE and TyG index are positively correlated. [38][39][40] There is a correlation between TyG index and prevalence of MACE in post-PCI populations; however, results of these studies have been inconsistent.…”
Section: Discussionmentioning
confidence: 99%
“…Second, TyG is usually associated with lipid and glucose metabolism disturbance, reflecting well the fat toxicity and sugar toxicity that can adversely affect cardiovascular outcomes (16,17). In addition, a higher TyG index is independently related to the occurrence and development of arterial stiffness, nephric microvascular damage and several diseases including hypertension, diabetes, stroke, coronary artery disease, non-alcoholic fatty liver and malignancy, which are identified as risk factors for early and late mortality in AAA patients after EVAR (4,(17)(18)(19). Therefore, it seems reasonable to propose that AAA subjects with higher TyG levels are more likely to experience a course of vascular and organ impairment, contributing to an increased risk of all-cause mortality after EVAR.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have evaluated the TGI in many areas, including its relationships with acute coronary syndrome in patients without [27][28][29][30][31][32][33] and with type 2 diabetes, [36] body mass index, [34,35] type 2 diabetes, [37][38][39][40][41] ischemic stroke, [41][42][43][44][45][46][47] cardiovascular disorders, [51][52][53] and intravenous thrombosis. [60,61] Like our study, some studies have examined the relationship between TGI and sarcopenia.…”
Section: Discussionmentioning
confidence: 99%
“…[40] Many recent studies have investigated the relationship between TGI and ischemic stroke, especially regarding cardiovascular disease. [41][42][43][44][45][46][47] The relationships between TGI and total chronic occlusion, [48] cancer, [49] and high blood pressure, [50,51] and the relationship between acute stroke and high blood pressure in older adults, have also been evaluated in detail. [52,53] While TMT and TGI have been used as separate parameters in different studies, we aimed to examine the relationships between these parameters and sarcopenia, mortality, and thirdmonth functional outcomes in patients after acute stroke.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation